Evaluating the English Textbook for Young Learners - Hertiki, Hertiki (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2019)
Evaluating the English textbook used at one of the National Plus Schools in Surabaya (SNA), this study aims at finding out whether Ã¢â‚¬Å“My Pals are Here!Ã¢â‚¬Â fulfill the objectives of teaching English and whether it is designed according to the principles of Teaching English to Young Learners (TEYL). Further, the instrument of this study was the researcher herself and equipped with an Evaluation Checklist by Bilash (2009). Also, an interview with a teacher who has used that book in class provided for this research. Using the checklist, it was found out that Ã¢â‚¬Å“My Pals are Here!Ã¢â‚¬Â is in accordance with the objective of teaching English at SNA, which is to help learners to be able to use English for communication especially orally. Ã¢â‚¬Å“My Pals are Here!Ã¢â‚¬Â is also fulfill the principles of TEYL